2017
DOI: 10.29238/kia.v11i2.38
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Mutu Pelayanan Kebidanan yang Mempengaruhi Tingkat Kepuasan Pasien di Poli Kebidanan RSUD Wonosari

Abstract: Hospitals play a role in improving the quality of health services. It was important to accurately measure patients' level of satisfaction.The previous study showed the score of 74.67%. It was lower than the level of customer satisfaction in Wonosari Regional PublicHospital (75.34%), 62.5% of the patients were satisfied of tangibles, 75% were satisfied on reliability, and 62.5% were satisfied inempathy. Research objective to investigate factors of midwifery service quality in Wonosari Regional Public Hospital M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The results of this study are in line with the findings of previous studies. Esthi's research (2017) confirms that the better the quality of care, the higher the level of patient satisfaction (Esthi et al, 2017). The findings of this study strengthen the understanding of the importance of quality midwifery care so that patient satisfaction with care is better (Andriani, 2017).…”
Section: Relationship Between Satisfaction Of Midwifery Care and Qualsupporting
confidence: 65%
See 2 more Smart Citations
“…The results of this study are in line with the findings of previous studies. Esthi's research (2017) confirms that the better the quality of care, the higher the level of patient satisfaction (Esthi et al, 2017). The findings of this study strengthen the understanding of the importance of quality midwifery care so that patient satisfaction with care is better (Andriani, 2017).…”
Section: Relationship Between Satisfaction Of Midwifery Care and Qualsupporting
confidence: 65%
“…The results showed that most of the samples expressed satisfaction with the care obtained during pregnancy to childbirth, mostly in the good category. Postpartum mother satisfaction with midwifery care is the perception of satisfac-tion of postpartum mothers with the quality of midwifery care provided from pregnancy, childbirth to postpartum (Esthi, et al, 2017).…”
Section: Postpartum Satisfaction With Midwifery Carementioning
confidence: 99%
See 1 more Smart Citation
“…bedakan serta perhatian yang diberikan)(Parasuraman et al, 2008). Hasil penelitian ini sejalan denganEsthi, Mindarsih and Murni (2017), yang menyebutkan bahwa ada hubungan antara dimensi pelayanan dengan tingkat kepuasan pasien. Pelayanan kebidanan sangat berpengaruh terhadap penilaian kepuasan ibu hamil sebagai penerima jasa di PMB(Djanah and Suherni, 2016) sedangkan kepuasan atas perilaku petugas menduduki urutan lebih tinggi dibanding dimensi kepuasan atas fasilitas/lingkungan (Mahendrawati dalam Djanah and Suherni, 2016).2) Fasilitas PelayananHasil penelitian menunjukkan bahwa ada hubungan antara fasilitas pelayanan dengan tingkat kepuasan ibu hamil.…”
unclassified